Blood lactate profile when highly qualified swimmers perform a special serial test - Kolganova, E. Y.; Golushko, T. V.; Fetisov, V. N.; Gridneva, E. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assessment of the relationship between the lactate profile and the level of development of special endurance, which determines the competitive results of highly qualified swimmers.